Inside Cover: Synthesis and Electrochemical Properties of Hierarchically Porous Zn(Co1−xMnx)2O4 Anodes for Li‐Ion Batteries (Energy Technol. 9/2017). Issue 9 (22nd May 2017) - Wong, Wei‐Ting; Chen, Bing‐Hong; Maggay, Irish Valerie B.; Liu, Chang; Duh, Jenq‐Gong; Liu, Wei‐Ren
Abstract : Anode for Li‐ion batteries : The cover image demonstrates the crystal structure, surface morphology and diffraction patterns of high‐stability Zn(Co1‐ x Mn x )O4 anode materials for Li‐ion batteries. It was first confirmed that ZnCo2 O4, ZnCo1.5 Mn0.5 O4, ZnCoMnO4, ZnCo0.5 Mn1.5 O4, and ZnMn2 O4 are isostructural and can form a solid solution. Compared to nano‐pore ZnCo2 O4 and macro‐pore ZnMn2 O4, as‐synthesized ZnCoMnO4 nanospheres exhibit a high capacity of 823 mAh g ‐1 with excellent cycling retention for more than 80 cycles without decay. The excellent cyclability might be due to the nanoscale particles and nature of the pore size distribution. This research not only proves that metallic doping methods can change the morphologies and the electrochemical performance of complex transition metal oxides with spinel cubic structure, but also reveals that the doping content of the metallic element is absolutely vital to achieving superior battery properties. More details can be found in the Full Paper by Liu and colleagues at Chung Yuan Christian University onpage 1526 in Issue 9, 2017 (10.1002/ente.201600634 ).